2012
DOI: 10.1186/1471-2180-12-131
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the heterotrimeric G-protein Gα, Gβ and Gγ subunits in the wheat pathogen Stagonospora nodorum

Abstract: BackgroundIt has been well established that the Gα subunit of the heterotrimeric G-protein in the wheat pathogen Stagonospora nodorum is required for a variety of phenotypes including pathogenicity, melanisation and asexual differentiation. The roles though of the Gγ and Gβ subunits though were unclear. The objective of this study was to identify and understand the role of these subunits and assess their requirement for pathogenicity and development.ResultsG-protein Gγ and Gβ subunits, named Gga1 and Gba1 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The S. nodorum genome encodes the necessary enzymes for lactose degradation, although the biochemical pathway consists of a number of low specificity enzymes. Importantly, however, as previously demonstrated, S. nodorum can utilize lactose as a sole carbon source (Gummer et al, 2012). The slower growth of the gga1-25 strain on lactose combined with the increased accumulation of this metabolite when grown on glucose suggests that lactose is geared towards anabolism in S. nodorum gga1-25, as may be the case with a number of the gga1 metabolites.…”
Section: G-protein Signalling In Stagonospora Nodorummentioning
confidence: 80%
See 4 more Smart Citations
“…The S. nodorum genome encodes the necessary enzymes for lactose degradation, although the biochemical pathway consists of a number of low specificity enzymes. Importantly, however, as previously demonstrated, S. nodorum can utilize lactose as a sole carbon source (Gummer et al, 2012). The slower growth of the gga1-25 strain on lactose combined with the increased accumulation of this metabolite when grown on glucose suggests that lactose is geared towards anabolism in S. nodorum gga1-25, as may be the case with a number of the gga1 metabolites.…”
Section: G-protein Signalling In Stagonospora Nodorummentioning
confidence: 80%
“…The recorded metabolite abundances therefore likely reflect both direct and indirect metabolic consequences of the mutation. In a previous study by this laboratory, we demonstrated that ongoing cold stress was sufficient to induce moderate levels of asexual sporulation in the mutant strains (Gummer et al, 2012). As previous sporulation studies in S. nodorum have highlighted the role of primary metabolism in this developmental stage (IpCho et al, 2010;Lowe et al, 2009;Solomon et al, 2005Solomon et al, , 2006cTan et al, 2008), metabolomics was again used to dissect the cold-induced response and identify which metabolites are specifically associated with asexual sporulation.…”
Section: Dissecting the Cold-induced Sporulation Phenomenonmentioning
confidence: 99%
See 3 more Smart Citations